THE SIGNIFICANCE OF MUSLIM FAMILIES AWARENESS IN PROMOTING ENTREPRENEURSHIP DEVELOPMENT IN SOKOTO STATE, NIGERIA - Hassan Malami Alkanchi,; Yusmini Binti Md Yusoff,; Ashraf Mohammed Zaidan, (Journal of Islamic, Social, Economics and Development, 2021)
Interest in promoting awareness of entrepreneurship development has beenincreasing worldwide for the advancement of economic development. Entrepreneurshipdevelopment has been considered a significant sector for economic development globally. Inrecent studies, literature that relates to the significance of promoting awareness forentrepreneurship development has been growing largely in the global village. Thus, studies onthe significance of entrepreneurship development for economic development have captured theattention of numerous experts. However, there are few or limited studies that explore theenormous role of Muslim families’ awareness of the significance of entrepreneurshipdevelopment in Sokoto state, Nigeria. The objective of this study is to explore the role of Muslimfamilies’ awareness in promoting entrepreneurship development in Sokoto state, Nigeria. Themethodology used for the conduct of this study is qualitative research. The study employed apurposive sampling technique and considered it the most suitable method for data collection.The data collection techniques employed for this study were interviews and focus groups. Thestudy used semi-structured interviews and focus group discussion for the data collection. Thestandard used for selecting the participants was strictly based on relevance, expertise,professionalism, and the willingness of the participants to participate in the study. Theparticipants interviewed include Muslim family experts, Muslim family counsellors, andIslamic scholars, comprising of five (4) participants for each research subject. Twelve (12)participants were sampled for the study. The method of data analysis used is thematic andtheoretical explanations. The study findings revealed that Muslim family awareness ofentrepreneurship development is very significant to economic development in Sokoto state,Nigeria. The data further reveals that Muslim families’ awareness through the media, Muslim scholars, and individual entrepreneurs strongly plays a pivotal role in promotingentrepreneurship for the economic development of the people of Sokoto state.